Governing clean energy transitions in China and India: A comparative political economy analysis - Karoliina Isoaho; Alexandra Goritz; Nicolai Schulz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
China and India will have to radically transform their electric power systems in order to decouple economic growth from unsustainable resource consumption. While the majority of transition literature has focused on the diverse socio-technical factors that could enable such a transformation, more recently scholars have called for a deeper analysis of political economy factors. This paper contributes to this approach by studying how a ruling coalition's ability and willingness to promote a clean energy transition is shaped by societal pressures, vested interests, and its power and cohesiveness. In doing so, we identify central drivers and barriers to a clean energy transition in China and India.
Keywords: Q42; Q55; Q56; O44; 330; green growth; state capacity; political settlement; ruling coalition survival; renewable energy policy; sub-national variation